English Teacher’s Strategies in Enhancing 9th Grade Students’ Critical Thinking at Junior High School 25 Muaro Jambi - Adang Ridwan; Ria Karmila (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research was to describe the English teacher’s strategies in enhancing the critical thinking skills of 9th grade students at Junior High School 25 Muaro Jambi. This study employed a qualitative descriptive method, with data collected through observation and interviews. The data were analyzed using the interactive model proposed by Miles and Huberman (1994), which includes data reduction, data display, and conclusion drawing/verification. The findings revealed that the teacher’s instructional strategies played a crucial role in fostering the development of students’ critical thinking skills. The teacher implemented various approaches such as posing open-ended questions, facilitating classroom discussions, conducting debates, and assigning writing tasks. These strategies were designed to promote analytical thinking and encourage students to express and defend their opinions. In addition to these core strategies, the teacher also used a combination of teaching methods, including reading comprehension exercises, translation and interpretation of texts, dictionary use, group work, dialogue practice, storytelling, vocabulary games, and writing simple essays for daily communication. These methods not only engaged students in active learning but also made the learning process more dynamic and enjoyable. As a result, students were able to think more clearly, quickly, and effectively, which significantly contributed to the development of their critical thinking abilities. The research concludes that a diverse and interactive set of teaching strategies can successfully enhance critical thinking among junior high school students. Teachers are encouraged to integrate a variety of methods tailored to students’ needs and classroom contexts to achieve optimal learning outcomes and better prepare students for higher-level thinking and problem-solving.